The impact of fitness social media use on exercise behavior: the chained mediating role of intrinsic motivation and exercise intention - Xiao, Xi; Huang, Dalin; Li, Guanchong (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to investigate the psychological mechanisms by which fitness social media use influences individuals’ exercise behavior, focusing on the chained mediating roles of intrinsic motivation and exercise intention.MethodsA cross-sectional online survey was conducted in April 2025 using snowball sampling, targeting social media users who regularly engage in physical activity. A total of 425 valid responses were analyzed. Constructs including fitness social media use, intrinsic motivation, exercise intention, and exercise behavior were assessed using validated Likert-scale instruments. Structural equation modeling and bootstrap analysis (5,000 resamples) were applied to test the hypothesized chained mediation model.ResultsFitness social media use was found to significantly predict intrinsic motivation (β = 0.396, p < 0.001), exercise intention (β = 0.254, p < 0.001), and exercise behavior (β = 0.295, p < 0.001). Both intrinsic motivation and exercise intention significantly mediated the relationship between social media use and exercise behavior. The chained mediation pathway was also supported, with indirect effects accounting for 33.55% of the total effect. Specifically, the indirect paths through intrinsic motivation (18.57%), exercise intention (10.75%), and the combined sequence (4.25%) were all statistically significant.ConclusionThese findings demonstrate that fitness social media use not only exerts a direct effect on exercise behavior but also influences it indirectly through a sequential psychological process involving emotional activation and cognitive planning. The study provides novel empirical evidence supporting the integration of Self-Determination Theory and the Theory of Planned Behavior, thereby offering a deeper understanding of how health behaviors form within digital contexts. In practical terms, this research highlights the significant role of social media–based digital platforms in enhancing intrinsic motivation and exercise intention. Future health-promotion interventions should therefore focus more explicitly on leveraging fitness social media to strengthen individuals’ intrinsic motivation and foster clear behavioral intentions, ultimately facilitating sustained engagement in physical activity and elevating overall population levels of physical activity.